1967
DOI: 10.2337/diab.16.4.264
|View full text |Cite
|
Sign up to set email alerts
|

Abnormally Increased Glomerular Filtration Rate in Short-term Insulin-treated Diabetic Subjects

Abstract: Functional changes in the microvascular system appear to precede the morphological changes in the conjunctiva and retina of young subjects with diabetes mellitus. Similar functional changes might occur in the renal microvascular system and hemodynamics and possibly lead to a disturbance in the glomerular filtration rate. A preliminary study of the glomerular filtration rate (GFR) using the radioactive vitamin B12 method in young, insulin-treated patients with short duration of diabetes is report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
38
0
1

Year Published

1979
1979
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(45 citation statements)
references
References 1 publication
6
38
0
1
Order By: Relevance
“…Several investigators have demonstrated an increase in PG synthesis in glomerular and mesangial cells in experimental diabetes, and some studies have postulated a role for vasodilatory PGs in the glomerular hyperfiltration observed in early diabetes (3,4). A similar trend was observed in our results of hyperglycemia-induced PGE 2 synthesis in HMCs, as shown in Fig.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Several investigators have demonstrated an increase in PG synthesis in glomerular and mesangial cells in experimental diabetes, and some studies have postulated a role for vasodilatory PGs in the glomerular hyperfiltration observed in early diabetes (3,4). A similar trend was observed in our results of hyperglycemia-induced PGE 2 synthesis in HMCs, as shown in Fig.…”
Section: Discussionsupporting
confidence: 79%
“…Glomerular hyperfiltration is a characteristic finding of early diabetes in both humans and animal models of diabetes and may play a major role in the pathogenesis of diabetic nephropathy (3,4). The mechanisms that mediate an increase in glomerular filtration rate are not well identified, but the vascular reactivity of the renal glomerular efferent arterioles has been shown to be controlled, at least in part, by the release of endogenously synthesized prostaglandins (PGs), allowing autoregulation of glomerular capillary pressure (5).…”
mentioning
confidence: 99%
“…These alterations constitute the characteristic features of diabetic microangiopathy [1]. While the morphological thickening of basal laminae has been well documented in various tissues [2][3][4][5][6], the biochemical and functional alterations, which concern the composition of basal lamina material and the loss of the filtration selectivity, accompanied by an increase in capillary permeability, have been well described only for the glomerulus and for a preparation of isolated capillaries [7][8][9][10][11][12]. However, a controversy has been raised concerning the biochemical changes occurring in the diabetic glomerular basal laminae [13].…”
mentioning
confidence: 99%
“…First, distinct glomerular lesions develop in patients with diabetes mellitus (1,2). Second, the glomerular filtration rate (GFR)' becomes higher than normal early in the course of juvenile onset diabetes mellitus while renal plasma flow remains normal, resulting in an elevation ofthe filtration fraction; filtration fractions averaging 28-30% have been reported (3)(4)(5). Because diabetes mellitus is a condition in which deficiency of insulin or tissue resistance to insulin exists, insulin may play some role in the regulation of glomerular function and metabolism.…”
Section: Introductionmentioning
confidence: 99%